2012
DOI: 10.3346/jkms.2012.27.3.285
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Treated Epilepsy in Korea Based on National Health Insurance Data

Abstract: The Korean national health security system covers the entire population and all medical facilities. We aimed to estimate epilepsy prevalence, anticonvulsant utilization pattern and the cost. We identified prevalent epilepsy patients by the prescription of anticonvulsants under the diagnostic codes suggesting seizure or epilepsy from 2007 Korean National Health Insurance databases. The information of demography, residential area, the kind of medical security service reflecting economic status, anticonvulsants, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 25 publications
0
26
1
1
Order By: Relevance
“…Our previous study demonstrated its value in estimating the national prevalence of epilepsy based on antiepileptic drugs (AEDs) prescribed and diagnostic codes for claims [1]. However, NHI data should be validated for epidemiological research [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study demonstrated its value in estimating the national prevalence of epilepsy based on antiepileptic drugs (AEDs) prescribed and diagnostic codes for claims [1]. However, NHI data should be validated for epidemiological research [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (WHO) estimates that 4-10 of every 1,000 people in the general population have epilepsy (WHO, 2016). The prevalence of treated epilepsy in Korea has been estimated to be 2.41 in every 1,000 people, with a higher prevalence in children (Lee et al, 2012). Antiepileptic drug (AED) therapy is the primary treatment for epilepsy.…”
Section: Aed Adherence In Childhood Epilepsymentioning
confidence: 99%
“…One-year AED prescribing patterns were described in a study using the NHIC database in Korea [20]. However, to the best of our knowledge, no study of the pediatric epilepsy population in Korea has described the initial and longitudinal AED prescription patterns.…”
Section: Introductionmentioning
confidence: 98%